Chicken Infectious Anemia Status in Commercial Broiler Chickens Flocks in Assiut-upper Egypt: Occurrence, Molecular Analysis Using PCR-RFLP and Apoptosis Effect on Affected Tissues - Mohamed, Moemen A. (International Journal of Poultry Science, 2010)
Chicken infectious anemia virus is ubiquitous virus of chickens causing disease in young chickens and immunosuppression in all birds. In the present study, the presence of chicken anemia virus CAV infection using PCR, genetic variability of isolated strains based on restriction of VP1 gene by Mbo1 and apoptotic changes in the CAV positive broiler chickens in Assiut region, Upper of Egypt, were investigated. The history of problem showed that the clinical features were depression, increased susceptibility to various diseases, vaccination failure and mortalities ranged from 4-21%. Postmortem findings were pale liver, atrophy of thymus and hemorrhages subcutaneously. These findings strongly suggested that CIAV may be the cause of the problem. DNA was extracted from thymus and bursa of fabricius of the collected birds and exposed to PCR assay. A total of 44 Chicken Infectious Anemia Virus (CIAV)DNA was detected genetically from 165 broiler chickens of age up to 7 weeks with a percentage 26.6%, which can be considered high and thus, reflects an attention demanding situation. The data show that restriction endonuclease analysis performed with the 1350-bp PCR product and the Mbo I enzyme indicated genetic variations among examined field isolates that two variants of the viruses having differences at genomic level were causing the disease in closely related regions of the province. Twenty five thymuses were collected and processed for DNA extraction. Cellular DNA was subjected to electrophoresis on 1.5% agarose gel and stained with ethidium bromide. Internucleosomal DNA fragmentation was detected in CIAV-infected tissues. These data indicated that infection with CIAV induced apoptosis in lymphoid cells that may affect solely on cellular immunity. Present findings thus highlights the significance of CIAV, therefore, focus should be made on CIAV epidemiology in the Upper Egypt and to further develop and apply reliable diagnostic tools as well as molecular studies so as to advise suitable prevention strategies for this economical important avian pathogen.